PENGARUH PERTUMBUHAN EKONOMI DAN KETIMPANGAN TERHADAP KESEJAHTERAAN MASYARAKAT DI KABUPATEN PANGKAJENE DAN KEPULAUAN - Sukri, Sukri Sukri (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2025)
Based on the research results, economic growth and income inequality both influence the level of community welfare in Pangkep Regency. Economic growth (<X1>) has a positive and significant influence on community welfare, with a beta coefficient of 0.652 and a significance of 0.001. This means that increasing economic growth tends to increase welfare. Income inequality (<X2>), as measured by the Gini Ratio, also shows a positive and significant influence on community welfare, with a beta coefficient of 0.193 and a significance of 0.044. This "positive" influence is surprising because usually higher inequality is associated with lower welfare. This conclusion suggests that in the context of Pangkep, the current slightly higher inequality may have an impact on improving overall welfare, although this is contrary to general theory. Simultaneously, both variables significantly influence welfare, as evidenced by the F value of 10,088.975 and a significance of <0.001. In conclusion, to improve welfare in Pangkep, it is important to encourage economic growth while trying to control inequality so that the benefits of growth can be felt by all levels of society.Keywords : Economic Growth, Inequality, Community Welfare